Dampak Kereta Api terhadap Pertanian dan Perdagangan di Jawa Barat, 1880-1930 - Muhammad Kautsar Thariq Syah; Putri Lailatus Sa'adah; Yan Nurcahya (Perkumpulan Program Studi Sejarah Se-Indonesia, 2026)
This study aims to analyze the role of railway transportation in supporting the movement of agricultural products and trade development in West Java during the Dutch colonial period. This research is significant because the growth of plantation commodities such as coffee, tea, sugar, and tobacco was closely linked to the availability of transportation infrastructure connecting production centers with export ports. This study uses a historical research method, collecting data from books, scientific journals, archival documents, and other historical sources relevant to the development of agriculture, plantations, and railways in West Java. The findings indicate that before the introduction of railways, agricultural commodities were transported using traditional methods such as carts, pack animals, and simple road networks, resulting in long travel times, high transportation costs, and a significant risk of product damage. The development of a railway network connecting plantation areas in Bogor, Sukabumi, Cianjur, Bandung, and other areas with Batavia and major ports substantially improved transportation efficiency. Railways accelerated the distribution of plantation products, reduced logistical constraints, increased export capacity, and encouraged economic integration between rural production areas and urban trade centers. The implications of this research indicate that transportation infrastructure plays a crucial role in agricultural commercialization, regional economic development, and market expansion. This study also demonstrates how the development of railways transformed patterns of commodity mobility and circulation in colonial West Java. The originality of this research lies in its focus on examining the relationship between railway expansion and the movement of agricultural commodities in West Java, a topic that has received little attention in previous historical studies.